2018
DOI: 10.1103/physrevlett.121.117001
|View full text |Cite
|
Sign up to set email alerts
|

Loss Mechanisms and Quasiparticle Dynamics in Superconducting Microwave Resonators Made of Thin-Film Granular Aluminum

Abstract: Superconducting high kinetic inductance elements constitute a valuable resource for quantum circuit design and millimeter-wave detection. Granular aluminum (grAl) in the superconducting regime is a particularly interesting material since it has already shown a kinetic inductance in the range of nH/□ and its deposition is compatible with conventional Al/AlOx/Al Josephson junction fabrication. We characterize microwave resonators fabricated from grAl with a room temperature resistivity of 4×10^{3}  μΩ cm, which … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
140
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 165 publications
(153 citation statements)
references
References 72 publications
5
140
2
Order By: Relevance
“…Quasiparticle fluctuations have been extensively studied [41], where the magnitude of frequency shifts scales with the kinetic inductance. Therefore, while they can be of order 100 kHz in disordered superconductors [45], they are much smaller in elemental superconductors. In fact, recent experiments [41] showed that the quasiparticles in aluminium produced an un-measurably small frequency shift; instead, the quasiparticles' influence was revealed only by examining correlated amplitude and frequency noise.…”
Section: Discussionmentioning
confidence: 99%
“…Quasiparticle fluctuations have been extensively studied [41], where the magnitude of frequency shifts scales with the kinetic inductance. Therefore, while they can be of order 100 kHz in disordered superconductors [45], they are much smaller in elemental superconductors. In fact, recent experiments [41] showed that the quasiparticles in aluminium produced an un-measurably small frequency shift; instead, the quasiparticles' influence was revealed only by examining correlated amplitude and frequency noise.…”
Section: Discussionmentioning
confidence: 99%
“…This behavior departs from the predictions of the BCS Mattis-Bardeen theory [5]. The enhanced low frequency dissipation has detrimental consequences on the quality factor of high impedance resonators that could be used in QC [6].…”
Section: Introductionmentioning
confidence: 62%
“…The inter-grain tunnel barriers lead to a sheet resistance of up to few kΩ which can be controlled during sample fabrication by adjusting the oxygen partial pressure during the film growth. Due to its low electrical loss, AlO x was recently proven to be very useful for implementing high kinetic inductances in quantum circuits [4] operated in the single photon regime [5]. In general, a wire made from AlO x can be seen as an alternating series of conducting grains separated by insulating barriers.…”
Section: Introductionmentioning
confidence: 99%